Assessing potency and binding kinetics of soluble adenylyl cyclase (sAC) inhibitors to maximize therapeutic potential - Rossetti, Thomas; Ferreira, Jacob; Ghanem, Lubna; Buck, Hannes; Steegborn, Clemens; Myers, Robert W.; Meinke, Peter T.; Levin, Lonny R.; Buck, Jochen (Frontiers in Physiology, 2022)
In mammalian cells, 10 different adenylyl cyclases produce the ubiquitous second messenger, cyclic adenosine monophosphate (cAMP). Amongst these cAMP-generating enzymes, bicarbonate (HCO3-)-regulated soluble adenylyl cyclase (sAC; ADCY10) is uniquely essential in sperm for reproduction. For this reason, sAC has been proposed as a potential therapeutic target for non-hormonal contraceptives for men. Here, we describe key sAC-focused in vitro assays to identify and characterize sAC inhibitors for therapeutic use. The affinity and binding kinetics of an inhibitor can greatly influence in vivo efficacy, therefore, we developed improved assays for assessing these efficacy defining features.